Persuasive character and panoptic organizational structure: the narratives of the National Book Institute and the Plan for the Dissemination of Bibliographic Works in Brazil - Oliveira, Alessandra Nunes de [UNESP]; Castro, Jetur Lima de [UNESP]; Ferreira da Silva, Luiz Eduardo (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
It investigates the narratives presented in the National Plan for the Dissemination of Bibliographic Works (PNDOB) on the measures for the implementation of the cultural dissemination of books and libraries in the Estado Novo in Brazil. Through the documentary appropriation of Gustavo Capanema's archive and newspapers at the time, the research went the way of Critical Discourse Analysis (ACD), based on the analysis of content and images on the paths and actions adopted by the National Book Institute (INL), with the objective of analyzing how the PNDOB occurred and was structured. The use of documentary sources was necessary to discuss how the actions of the INL were widely disseminated in a persuasive and panoptic structure, through which the PNDOB was established with the objective of monitoring and controlling the books, applied to the disciplinary institution, aiming at correction and order in the name of morals and good customs. For this reason, it was questioned to what extent it is possible to consider that the publications and initiatives created by the INL were beneficial to society in the Estado Novo period, because, even though there was all the apparent dissemination of books and libraries, other types of books were considered harmful to society and sought in all corners of Brazil to get out of circulation. The results indicated the PNDOB of the INL with a persuasive and panoptic structure and a volume close to 88 sheets, among numerous graphs, organization charts and planning. It is concluded that it is possible to think about whether the actions of the INL found a beneficial attitude, since it was organized in detail in favor of education and the varguista culture of the constant expansion of information under the order of bibliographic control, and how access to knowledge and information policies happened through books in Brazil.
Keywords: Estado Novo - Brazil; Instituo Nacional do Livro; Censorship; Control of bibliographic works